Father Reflections on Their Involvement With Primary School Students: Connections to School Literacy Learning. (November 2019) - Lynch, Jacqueline
Father involvement in children's education is known to have increased over the years, yet less is known about their involvement with children outside of school, particularly after children attend formal schooling. Such information could provide more knowledge of children's literacy engagement in schools as well as have implications for future teaching practice. Another goal was to gain insight on fathers' recommendations for schools in order to assist student learning. There were 13 fathers from culturally diverse backgrounds who volunteered for a 30–40 minute interview. Three themes were found: (1) shared father–child interests and practice, (2) importance of student interest and choice in school, and (3) student writing difficulties and self-concept issues. Following father interviews, teachers were invited for a short interview in order to gather knowledge on their perspectives on student engagement and literacy teaching and learning. Two Grade 2 teachers consented, and two themes were revealed: (1) children's motivation for reading and writing in school and (2) teacher knowledge of father–child interactions. Following father and teacher theme comparisons, recommendations were suggested for both home and in-school learning. Considering the deficiency in current knowledge of fathers' practices and perspectives, this research offers further insight on father interactions with children and their perspectives for school learning.